2015
DOI: 10.1017/s0263034615001032
|View full text |Cite
|
Sign up to set email alerts
|

Electron acceleration at grazing incidence of a subpicosecond intense laser pulse onto a plane solid target

Abstract: Generation of hot electrons at grazing incidence of a subpicosecond relativistic-intense laser pulse onto a plane solid target is analyzed for the parameters of petawatt class laser systems. We study preplasma formation on the surface of solid aluminum targets produced by laser prepulses with a different time structure. For modeling of the preplasma dynamics, we use a wide-range two-temperature hydrodynamic model. As a result of simulations, the preplasma expansion under the action of the laser prepulse and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…It was shown that a preplasma of a near critical electron density supports the generation of a significant fraction of MeV electrons [9][10][11]. Simulations of the MeV-electron spectral distribution and fraction in dependence on the preplasma scale length L p made in [12] showed dramatic increase in the hot electron temperature and conversion efficiency by increasing of the plasma scale length from L p =50 up to 500.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a preplasma of a near critical electron density supports the generation of a significant fraction of MeV electrons [9][10][11]. Simulations of the MeV-electron spectral distribution and fraction in dependence on the preplasma scale length L p made in [12] showed dramatic increase in the hot electron temperature and conversion efficiency by increasing of the plasma scale length from L p =50 up to 500.…”
Section: Introductionmentioning
confidence: 99%
“…However, those schemes require an external electron injector which should be synchronized with the laser pulses on a femtosecond scale. Another approach is based on the interaction of a laser pulse with dense planar targets [16][17][18][19][20][21][22], structured targets [23][24][25] or waveguides [26 and 27], which allows production of subfemtosecond multi-MeV electron bunches which usually a) Electronic mail: dms@appl.sci-nnov.ru have high charge because of the high electron density of the target. Producing such sources of energetic electron bunches is of much interest among experimentalists over the last few years [20, 23, 24, and 28].…”
Section: Introductionmentioning
confidence: 99%
“…The targets range from solid density with sharp boundaries to extended low density gas. In solids, the mechanism strongly depends on the gradients of the pre-plasma on the target surface and can be the vacuum/Brunel [7], resonant absorption in critical density, the ponderomotive and the (J×B) mechanism of acceleration [8,9] or stochastic heating [10][11][12][13] etc. Laser interaction with low density gas targets provides an effective acceleration of electrons to high energies in the wakefields generated in preformed plasma channels [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There are different mechanisms of laser energy transfer to high energy electrons depending on the laser parameters and the type of targets from solid density targets with sharp boundary to extended low density gas targets. In solids, the mechanism strongly depends on gradients of the preplasma on the target surface and can be the vacuum/Brunel [7], resonant absorption in critical density, the ponderomotive or (JxB) mechanism of acceleration [8,9], stochastic heating [10][11][12][13] etc.…”
Section: Introductionmentioning
confidence: 99%